Fotoperiodismo en el despertar del siglo XX mexicano: bajo la mirada del dictador - Rebeca Monroy Nasr (Caravelle)
This essay aims to determine some photographic parameters which have been established and applied by press photography during the Victoriano Huerta’s presidency (February 9 1913-July 15 1914). We shall observe how the editors, photographers and writers of the magazine La Semana Ilustrada behaved in order to determine how the words and images were moulded to fit Huerta’s interests. We shall also underline the iconographic and political changes which have carried on mistakes or, on the contrary, have introduced new habits in editorial work. Finally, we shall observe how the basis of a visual nationalism, which has extended to the graphic productions of the post-Revolution, was established then.